Associated factors and virologic outcomes of cisgender groups among people living with HIV/AIDS attending a tertiary health facility in Rivers State, Nigeria - Luke, Anwuri; Owhonda, Golden; Ogbondah, Bright O.; Tobin-West, Charles I. (International Journal Of Community Medicine And Public Health, 2022)
Virologic outcome is the assessment of an human immuno-deficiency virus (HIV)-positive patient response antiretroviral therapy adherence using real-time polymerase chain reaction assays after two consecutive viral load measurements ≥3 months apart. This study aimed to assess the associated factors of virologic outcomes among cisgender groups of people living with HIV/AIDS attending a tertiary health facility in Rivers State, Nigeria. This comparative cross-sectional study was conducted at the antiretroviral therapy clinic of the University of Port Harcourt Teaching Hospital from September 2020 to November 2020. The systematic sampling technique was employed to select 1600 participants; females (800), and males (800). Data was collected using a 3-item structured interviewer-administered questionnaire. Statistical package for social science (SPSS) version-25 was used to analyze data. Test of association was done using Chi-square, Fisher’s exact and spearman rho test and set at a significance level of p<0.05 and 95% CI. Confounding variables were controlled using multiple logistic regression analysis. A total of 1600 participants; males (800), and females (800) were recruited. The study reported a mean age and standard deviation: male (44.53±10.50), female (40.58±9.34); virologic suppression levels; male (89.5%), female (89.6%). Having a treatment supporter (aOR=0.382; 95% CI=0.206-0.707; p=0.002) among the female gender was influenced by virologic outcome. The cisgender female group had slightly better virologic outcomes as opposed to the cisgender male group and this was significantly influenced by having a treatment supporter. Therefore, PLWHA should make personal efforts to participate in adherence counselling sessions and other HIV/AIDS support services offered at the ARV therapy clinics.